Evaluation innovative companies of the defense industry - ФедороваЕлена Анатольевна; МазаловЕвгений Сергеевич; ТкаченкоАнастасия Андреевна; ФёдоровФёдор Юрьевич (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2015)
Elena Anatolievna Fedorova - Financial University at the Government of the Russian Federation. E-mail: ecolena@mail.ru Evgeny S. Mazalov - Federal State Educational Budgetary Institution of Higher Professional Education "Financial University under the Government of the Russian Federation". E-mail: e.mazalov@yahoo.com <span data-sheets-value=""1":2,"2":"Anastasia Andreevna Tkachenko - Federal State Educational Budgetary Institution of Higher Professional Education "Financial University under the Government of the Russian Federation". Email: anastasia270791@yandex.ru"" data-sheets-userformat=""2":513,"3":[null,0],"12":0">Anastasia Andreevna Tkachenko - Federal State Educational Budgetary Institution of Higher Professional Education "Financial University under the Government of the Russian Federation". Email: anastasia270791@yandex.ru Fedor Y. Fyodorov - National Research University "Higher School of Economics". In this study, estimated operating (profitability) and technical efficiency of enterprises of the military-industrial complex. The empirical base includes financial and economic indicators 1425 of defense enterprises, research method is a nonparametric method DEA (Data Envelopment analysis). Based on the conducted analysis revealed: 1) it is impossible to evaluate the performance of the MIC based only on technical efficiency. An entity may have low profitability, but due to production specifics, to work more efficiently. 2) enterprises with a high share of state participation (85-100%) work more efficiently in connection with the modernization of basic production assets and increasing contract base by government programs. 3) Enterprises with a contractual base of over 500 million rubles, have a higher margin (5.1 per cent) than enterprises with a contractual base of less than 500 million rubles (-104%). 4) sanctions imposed by Western countries against Russian defense enterprises, are unable to significantly affect technical efficiency of enterprises in 2014.